Bread wheat varieties influenced by different levels of Nitrogen and phosphorous grown in calcareous soil - Al-Falah, Mohammed Ali Hussain; Sedqi, Mohammed; Dohuki, Salih M. (Sulaimani Journal for Pure and Applied Sciences, 2014)
Field trails were conducted at the field of the Faculty of Agriculture and Forestry/ university of Duhok/ Semmel District- Duhok Governorate/ Kurdistan region/ Iraq, which located in semi-arid zone, during seasons 2008-2009 and 2009-2010, to study the effect of different levels of Nitrogen and Phosphorous (0.0, 60, 120, and 180) kg N. ha-1 ,(0.0, 183.2, 229.0, and 274.8) kg P2O5. ha-1respectively, on leaf area (cm2), plant high (cm), number of spikes. plant-1, number of grains. spike -1, 1000 grain weight, grain yield (g). plant-1, of two varieties (Rezgary and Fateh) under rain feed conditions, in silty clay texture soil (classified as Vertisols), characterized as high calcium carbonate, low organic matter content and high pH value. The results showed highly significant effect of year in all studied traits with exception number of grains per spike and the varieties exhibited highly significant effect in plant height, leaf area, 1000 grain weight and grain yield . plant-1. The interaction effect between Nitrogen, Phosphorous, and varieties, shows highly significant effects for all traits except number of grains. spike-1. Alsointeraction effects between (Years × Variety × Nitrogen × Phosphorous) gave high significant effects in all studied traits with exception of plant height and number of grains. spike-1.
Keywords: Bread wheat varieties; Nitrogen; Phosphorous levels; grain yield